Peran Mahasiswa KKN UINSU dan Perangkat Desa dalam Mengatasi Stunting dan Buta Huruf Al-Qur’an di Nagori Lingga Kec. Gunung Malela Kabupaten Simalungun - Muhammad Febrian; Jeni Yulinda; Regita Cahyani; Kherina Surya Ningsih; Yusuf Ramadhan Nasution (MODELING: Jurnal Program Studi PGMI, 2023)
The role of uinsu KKN students and the Lingga village apparatus, Gunung Malela sub-district, Simalungun district in overcoming stunting and illiteracy of the Qur'an in children in Lingga village went very smoothly. Uinsu KKN students totaling 25 people. With 4 men and 21 women with village officials participating in disseminating information about the importance of preventing stunting from an early age, the village community also helps and collaborates with students in introducing and teaching the letters of the Qur'an. to children in the village, especially to children who do not know how to read the Qur'an at an old age. This happens because children from childhood have been given by their parents with smartphones and parents are also quite indifferent to their children's religious education.